A Method to Guide Pressure Selection for Programmable Pressure Valves after Ventriculoperitoneal Shunt Surgery - Zhang, Hongri; Fan, Chen; Bi, Haojie; Hao, Xiaowei; Peng, Jinghua (Asian Journal of Neurosurgery, 2025)
Programmable pressure valves with antisiphon/gravity devices are recommended for ventriculoperitoneal shunts. However, cerebrospinal fluid (CSF) overdrainage and underdrainage still frequently occur because of the lack of effective pressure regulation methods. Therefore, this study aimed to provide a method to guide valve pressure selection after ventriculoperitoneal shunt placement.A total of 31 patients whose valve pressure was lowered for the last time after ventriculoperitoneal shunt placement were enrolled in this study. Glucose solution was injected into the reservoir before and after adjustment, and the residual glucose concentration was measured 20 minutes later. Residual glucose concentrations were then compared between before and after adjustment. In vitro experiments were also conducted to simulate the flow of CSF through the shunt valve and detect the relationship between flow rate and residual glucose concentration.The glucose concentration in the CSF was significantly decreased after adjusting (mean ± standard deviation, 15 ± 6.6 vs. 5.6 ± 3.1 mmol/L, respectively; p < 0.01).When the residual glucose concentration is higher than 10 mmol/L, an underdrainage shunt should be considered, and when it is lower than 10 mmol/L, an appropriate pressure should be considered, which provides a reference for lowering the shunt valve pressure.
Keywords: programmable pressure; hydrocephalus; ventriculoperitoneal shunts; cerebrospinal fluid; underdrainage